Flying activity and population dynamics of Cordulegaster heros Theischinger, 1979 (Insecta: Odonata: Cordulegastridae) in Slovakia. Issue 2 (2nd April 2020) - Balázs, Attila; Fric, Zdeněk F.; Holuša, Otakar
Abstract : In 2017, we investigated the population dynamics and flying activity of the south-east European endemic dragonfly species Cordulegaster heros Theischinger, 1979. This research was conducted in the southern part of Central Slovakia in the Revúcka vrchovina Upland at a submountainous stream called Drienok. The mark-release-recapture method was applied to study the population. Cordulegaster heros was observed 775 times during the midsummer season. We found out that the species has bimodal diurnal activity pattern with a highest peak from 17:00 until 19:00 hours, but the species had a short peak before noon as well. The differences between sexes in the sense of entering new individuals to the population were low during the main flying period. Estimated population size for males surpassed the population size of females. Probability of capture decreased by the end of the flying season without differences in sexes. This article is the first on the flying activity and population dynamics of Cordulegaster heros .